Bipolar charging and neutralization of particles below 10 nm, the conditions to reach the stationary charge distribution, and the effect of a non-stationary charge distribution on particle sizing. (February 2020) - Ibarra, I.; Rodríguez-Maroto, J.; Alonso, M.
Abstract: Bipolar charging and neutralization of aerosol particles with diameter below 10 nm in a circular tube with uniform ion-pair generation have been studied theoretically to determine the conditions required to reach the stationary charge distribution. In order to reach the stationary distribution the initial ion-to-aerosol number concentration ratio, N i n / n i n, and the N i n τ product ( τ is the mean aerosol residence time in the charger) must both be sufficiently large. These parameters can be combined in a single dimensionless parameter, β N i n 2 τ / n i n, where β is the attachment rate coefficient between a charged particle and an ion of opposite polarity. Attainment of the stationary distribution requires that this dimensionless number be larger than about 800 for neutralization of charged particles, and larger than about 500 for charging of uncharged particles. Experiments have shown that the stationary charge distribution cannot be reached neither using low cost, low activity 241 Am sources nor a commercially available and widely used 2 mCi 85 Kr neutralizer. When particle sizing by mobility analysis is carried out employing a charger in which the stationary charge distribution is not reached, inversion of the mobility distribution assuming that the charge distribution on the particles is the stationary one yields correct values of the mean particle diameter and the standard deviation, but fails to predict the aerosol number concentration. Highlights: Attainment of the stationary charge distribution is controlled by a single dimensionless coefficient. Stationary charging state is not reached with a low activity radioactive source. Stationary charge distribution cannot be achieved with a 2 mCi Kr85 commercial neutralizer. Size distribution mean and width are accurately retrieved even with a non-stationary charger.